Developing effective student learning environment: Case study from Sharjah, United Arab Emirates - Solovieva, Nadia; Dani, Anita; Kane, Patrick; Thomson, Sophy; Hamam, Doaa; Solaimani, Fares Keramatulah (Frontiers in Education, 2022)
The impact of Covid-19 on college education has been profound. At the same time, it has also provided an opportunity to test the effectiveness of new teaching approaches in challenging circumstances when the new delivery modes were introduced. In this case study, we have taken the project-based learning approach a little further by directly involving students as co-researchers in the ongoing research project on Sharjah women’s campus, Higher Colleges of Technology. This campus-based research project aimed at finding effective solutions to reduce plastic waste on Sharjah women campus. We enabled several groups of students to participate in the primary data collection for our project by aligning their course work projects with the aims of our own research. Hence, the students were directly involved in the ongoing community project, which raised their awareness about important sustainability issues. In addition, the students have acquired essential research skills and were able to apply their knowledge to the practical issue. This approach was effective: the difference between the final grades of students in project and non-project groups was statistically significant in 2020 and in 2021. In 2020, the students in the project group scored 5.16% higher than the students in non-project group. (95% confidence interval is [-0.9044, 11.2244], p=0.047). In 2021, this difference was 6.5% (95% confidence interval is [2.1176, 10.9026], p=0.002).